2011
DOI: 10.5402/2011/516969
|View full text |Cite
|
Sign up to set email alerts
|

Cephalometric Evaluation of the Effect of Complete Dentures on Retropharyngeal Space and Its Effect on Spirometric Values in Altered Vertical Dimension

Abstract: Role of complete dentures in reducing apnea-hypoapnea index in edentulous obstructive sleep apnea patient has shown promising results in previous studies. This study was undertaken to ascertain the role of complete denture and complete denture with slight increase in vertical dimension using custom made occlussal jig, on retropharyngeal space, posterior airway space, pharyngeal depth, and spirometric readings in comparison with those in edentulous group. Significant changes were observed in both intervention g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 17 publications
(26 reference statements)
0
24
0
6
Order By: Relevance
“…Among 403 older individuals, 71% of those who did not wear their prostheses at night were at high risk for obstructive sleep apnea (Gassino et al , ). Sleeping without prostheses is associated with a significant increase in the AHI (Buysse et al , ; Bucca et al , , ; Erovigni et al , ; Gassino et al , ; Gupta et al , ; Emami et al , ).…”
Section: Sleep Disorders Oral Health and Oral Functionmentioning
confidence: 99%
“…Among 403 older individuals, 71% of those who did not wear their prostheses at night were at high risk for obstructive sleep apnea (Gassino et al , ). Sleeping without prostheses is associated with a significant increase in the AHI (Buysse et al , ; Bucca et al , , ; Erovigni et al , ; Gassino et al , ; Gupta et al , ; Emami et al , ).…”
Section: Sleep Disorders Oral Health and Oral Functionmentioning
confidence: 99%
“…Maintenance of occlusal support protects against atrophy of masseter muscle fiber thickness and volume, especially in the premolar region [25]. Moreover, dentures restore the vertical dimension of occlusion, lower facial height, retropharyngeal and posterior airway spaces, and peak inspiratory flow rates [11, 28]. …”
Section: Discussionmentioning
confidence: 99%
“…Gupta et al [4] evaluated completely edentulous patients cephalometrically with increasing vertical jaw relation using an acrylic jig of 2 mm to 3 mm and revealed that there was a statistically significant correlation between PAS and retropharyngeal space between edentulous and patients with complete dentures and they concluded that increasing vertical dimension of occlusion within acceptable limits is beneficial to patients with OSA.…”
Section: Discussionmentioning
confidence: 99%
“…Complete tooth loss sequels in anatomical changes that may sway upper airway dimensions and pass out by influencing the postural rest position of the mandible, muscle tone and tongue posture during sleep. A decrease in retropharyngeal space and or the hypotonicity of the pharyngeal musculature in edentulous people have been recommended to increase the collapsibility of airways [4].…”
Section: Introductionmentioning
confidence: 99%